Urgensi Pendidikan Praktik Berkuda Dan Memanah Dalam Meningkatkan Kecerdasan Emosional Santri Di PPTQ Qoryatul Qur’an - Muhammad Ikhsannudin; Joko Sarjono; M. Fatchurrohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Furusiyah or equestrian sport is the ability to ride a horse and control it wherever the horse moves or runs. In general, the meaning is the science of dexterity in playing weapons on a horse or without a horse. This knowledge is considered a natural classic sport and has been very popular with Arab people since ancient times until now. Because horse riding was very important to the Arabs they taught their children from an early age to practice horseback riding and archery. In the history of the hadith that Rasulullah Shallallahu Alaihi Wasallam once raced a horse and competed with other horses. He once rode a black mare and then spurred her with both legs to say that this horse was running very fast. The person who first taught the science of furusia was Nabiyullah Ismail Alaihissalam at that time horses were wild like other wild animals. Then Allah tamed the horse and it could be ridden by Prophet Ismail Alaihissalam. Because of the diversity of horses, said Syarif Ahmad Al Hamawi in his book Annafhatul Miskiyah fii Sinaatil Furusiyah, he said,